Principal’s Leadership in Teacher’s Performance Development - Rusmita, Rusmita; Fitria, Happy; Mulyadi, Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2023)
This study was conducted to find out and describe the principal’s leadership in fostering teacher’s performance at SMA Negeri 3 Banyuasin III. The research method is a qualitative with a descriptive approach. Data collection techniques used: (1) observation; (2) interviews; (3) run. Research data analysis techniques: (1) data reduction; (2) data presentation; (3) conclusion and verification. Based on the results of the research it is known that: the principal plays an active role, in fostering teachers in preparing lesson plans, teachers in carrying out learning are in accordance with the curriculum. The teacher assesses learning outcomes every midterm, and per semester. The obstacle faced by school principals and teachers is the lack of learning resource facilities as supporting media for teachers in conveying learning, so that the learning process delivered does not work as expected and is less than optimal. The strategy carried out by the principal is by empowering the ability of teachers and utilizing makeshift learning resource facilities with a strategy of providing examples related to the daily lives of students in the real world related to the learning material delivered refers to active, innovative learning, which is creative, effective and fun.